CHARACTERISTICS OF PHYSICOCHEMICAL GELATIN OF SNAKEHEAD (Channa striata) FISHBONES EXTRACTION WITH BROMELAIN ENZYME - Yuliana, Yuliana; Karnila, Rahman; Sukmiwati, Mery (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTSnakehead fish is one of the fish that has many benefits, almost all parts of its body can be used,such as the bones. Fishbones are one of the raw materials for gelatin. This studyaimed to determine the effect of the use of bromelain enzymes on the characteristics of snakehead fishbone gelatin using a non-factorial completely randomized design (CRD) with 3 treatment levels, namely E1 (2% bromelain enzyme), E2 (4% bromelainenzyme) and E3 (6%bromelainenzyme). The parameters of analysisconsisted of yield, viscosity, isoelectric point, pH, and chemical composition (moisture, ash, and protein content). The results showed that the yield of gelatin extracted with the bromelainenzyme with concentrations of 2, 4, and 6% was 3.81-3.06%. Gelatin had a viscosity of 1.97-3.07 cP, its isoelectric point was at pH 7.5 with the lowest protein solubility, and the pH of gelatin ranges from 5.52 – 6.21. The chemical composition of snakehead fish bone gelatin contained moisture, ash, and protein content ranging from 4.08-7.45% (ww), 1.64-3.29% (ww), and 62.39-80.53% (ww). The best treatment of gelatin extraction with bromelain enzyme using concentration of 6% resulted in the highest yield of 3.56%, viscosity 2.06 cP, isoelectric point 8.77, pH 6.21 and protein 80.53%. Keywords:bone of snakehead fish, concentration of enzyme, gelatin